Analisis Pengaruh Literasi Membaca Terhadap Kemampuan Matematika Di Tinjau Dari Data PISA 2022 - Ika Febriana; Ameliya Ameliya; Cindy Angelina Saragi Napitu; Mutia Agustin Purba; Yumna Khairi Amani Piliang (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This research focuses on the relationship between reading and mathematics abilities using PISA 2022 data. The importance of literacy and numeracy as the main foundation for student development is the starting point for this research. In the midst of Indonesia's challenges in building a culture of literacy, especially at the elementary school level, this research explores the relationship between reading and mathematics abilities through analysis of PISA 2022 data. Secondary data from the PISA 2020 survey and regression analysis techniques are used to explore this relationship. The analysis results show a significant correlation between these two abilities, with a strong and positive correlation coefficient. These findings indicate that students with good reading skills tend to have better math skills. In conclusion, it is important to build literacy and numeracy from an early age at the elementary school level to prepare students to face more complex material. This research suggestion includes the development of integrated literacy and numeracy programs, updating the mathematics curriculum, teacher training, strengthening parental involvement, use of educational technology, as well as further research to understand the factors that influence the relationship between reading literacy and mathematics ability.